Intimacies and distances: mobility, belonging and the use of information and communication technologies by young Cameroonians in Cape Town - Jackson, Kate (Social Anthropology, 2014)
Advances in Information and Communication Technologies (ICTs) are making it increasingly easy to build and maintain social links across distance, by effecting a compression of space and time, and allowing friends and family members to remain in ever-closer contact, even though they may live geographically far apart. These distanced relationships facilitated by ICT represent an important site of anthropological inquiry, even as they present methodological challenges to the accepted conceptions of fieldwork and the field. In this thesis I present the results of an ethnography of the use of ICT by Cameroonian students living in Cape Town, South Africa between June 2011 and June 2013. The research question guiding my work reads as follows: "Do (and if so, how do) Cameroonian students in Cape Town transcend geographical and social boundaries through their use of information and communication technology?" I argue that the Cameroonian students who I met during my fieldwork in Cape Town used ICTs to build and maintain relationships within their community (or multiple communities), and to draw upon their social networks to (re)negotiate and transcend geographical and social boundaries. I also argue that while they do this they simultaneously contest and reinforce hierarchies of various forms, be they politico-geographical, social or economic. In the course of my fieldwork, it became increasingly evident that the young people who helped me in my inquiries used these technologies to intimately entangle, as well as distance, themselves from others in their communicative environment and relationships. I draw on my fieldwork to illustrate the ways in which they do this. I argue that these people negotiated relationships of marginality, belonging, obligation and responsibility through the ways in which they used ICTs, and that they drew on the functions of ICTs, particularly the social networking site, Facebook, to actively construct their identities. I conducted the main body of my fieldwork between June 2011, and June 2012. However, at the time of submitting the draft of my thesis in July 2013, I was still in contact with the people who helped me in my research, and therefore was engaged in fieldwork throughout the course of the research and writing process. This study forms part of a larger project entitled: "Information and Communication Technologies (ICTs), mobility and the reconfiguration of marginality in South(ern) Africa". I hope to contribute to this larger project with this ethnographic study of the use of ICTs by Cameroonian students in Cape Town in the context of their mobility, varying levels of marginality, and their social networks and community relations, by seeking to answer the research question.